Design of monolithic concrete foundation slabs with FRP reinforcement - K. L. Kudyakov; A. V. Buchkin (Vestnik MGSU)
Introduction. Over the past decade, the share of concrete structures reinforced with composite polymer reinforcement (FRP) has increased, which is due, among other things, to the development of the regulatory and technical framework in this direction. The inherent features of FRP, largely determined by the properties of its components, which must be taken into account at all stages of construction and operation of the building, lead to some changes in the traditional approaches to the design of structures and the technology of their construction.Materials and methods. A review of domestic experience in the use of composite polymer reinforcement in the construction of monolithic concrete foundations is carried out. An example of design and construction solutions of a foundation plate is considered. On the basis of its analysis, the selection of reinforcement from FRP was carried out according to the results of calculations for the first and second groups of limit states.Results. Design features that should be taken into account when calculating foundation slabs made of concrete reinforced with FRP are indicated. The concrete example of a monolithic concrete foundation slab shows the effect of taking into account the actual mechanical characteristics of FRP on the results of strength and crack resistance calculations. The results of calculations carried out according to various editions of regulatory documents relevant for the period from 2014 to 2023 clearly demonstrate the development of the regulatory framework in terms of taking into account the FRP properties in reinforced concrete structures.Conclusions. With a rational approach to design processes, it is possible to develop projects of concrete foundation slabs on an elastic base using FRP that meet the requirements of regulatory documents on reliability. It is possible to completely exclude metal elements (fittings, products, embedded parts) in such structures.